Levantamiento, definición e implementación de la Capa de Negocio de MALCA Cía. Ltda., utilizando la descripción del modelado arquitectónico ADM-TOGAF - Alvarado Hidalgo, Oswaldo Alejandro. (2015)
Survey, defining and implementing the Business Layer of the Sugar Company MALCA Cía Ltda., is focused on strengthening the business area and improve IT governance that currently owns the company, applying the guidelines of the method of architectural development ADM of the TOGAF architecture framework. This work allows the company to define, and to be clear the elements keys of the business, also allows establish the business baseline and the ideal state of the business. For this work has been referred to the Architecture Development Method of TOGAF v9, in its preliminary stages, vision, business there are a set of guidelines, supported by architectural artifacts and deliverables establishing the necessary bases for the architectural development at all levels. Based on this, we‘ll develop a reference framework that supported by a suite of products allows the Empresa Azucarera MALCA Cía. Ltda. (or also called Grupo Empresarial Monterrey GEM) understand the key concepts of architectural practice that has developed in the company and take the decision of its adoption.